Interictal PET and ictal subtraction SPECT: Sensitivity in the detection of seizure foci in patients with medically intractable epilepsy. (2nd October 2012) - Desai, Atman; Bekelis, Kimon; Thadani, Vijay M.; Roberts, David W.; Jobst, Barbara C.; Duhaime, Ann‐Christine; Gilbert, Karen; Darcey, Terrance M.; Studholme, Colin; Siegel, Alan
Summary Purpose: Interictal positron emission tomography (PET) and ictal subtraction single photon emission computed tomography (SPECT) of the brain have been shown to be valuable tests in the presurgical evaluation of epilepsy. To determine the relative utility of these methods in the localization of seizure foci, we compared interictal PET and ictal subtraction SPECT to subdural and depth electrode recordings in patients with medically intractable epilepsy. Methods: Between 2003 and 2009, clinical information on all patients at our institution undergoing intracranial electroencephalography (EEG) monitoring was charted in a prospectively recorded database. Patients who underwent preoperative interictal PET and ictal subtraction SPECT were selected from this database. Patient characteristics and the findings on preoperative interictal PET and ictal subtraction SPECT were analyzed. Sensitivity of detection of seizure foci for each modality, as compared to intracranial EEG monitoring, was calculated. Key Findings: Fifty‐three patients underwent intracranial EEG monitoring with preoperative interictal PET and ictal subtraction SPECT scans. The average patient age was 32.7 years (median 32 years, range 1–60 years). Twenty‐seven patients had findings of reduced metabolism on interictal PET scan, whereas all 53 patients studied demonstrated a region of relative hyperperfusion on ictal subtraction SPECT suggestive of an epileptogenic zone. Intracranial EEG monitoring identified a single seizure focus in 45 patients, with 39 eventually undergoing resective surgery. Of the 45 patients in whom a seizure focus was localized, PET scan identified the same region in 25 cases (56% sensitivity) and SPECT in 39 cases (87% sensitivity). Intracranial EEG was concordant with at least one study in 41 cases (91%) and both studies in 23 cases (51%). In 16 (80%) of 20 cases where PET did not correlate with intracranial EEG, the SPECT study was concordant. Conversely, PET and intracranial EEG were concordant in two (33%) of the six cases where the SPECT did not demonstrate the seizure focus outlined by intracranial EEG. Thirty‐three patients had surgical resection and >2 years of follow‐up, and 21 of these (64%) had Engel class 1 outcome. No significant effect of imaging concordance on seizure outcome was seen. Significance: Interictal PET and ictal subtraction SPECT studies can provide important information in the preoperative evaluation of medically intractable epilepsy. Of the two studies, ictal subtraction SPECT appears to be the more sensitive. When both studies are used together, however, they can provide complementary information.